ANALISIS PENERAPAN PROGRAM KESELAMATAN KERJA DALAM USAHA MENINGKATKAN PRODUKTIVITAS KERJA DENGAN PENDEKATAN FAULT TREE ANALYSIS DAN HAZARD AND OPERABILITY STUDY - Yetti Meuthia Hasibuan; Rini Halila Nasution; Uun Novalia Harahap; Rafika Apriani Pratiwi; Wan Krisman Hia (Universitas Harapan Medan, 2021)
PT. Sumatra Hakarindo in its operation is not free from problems encountered such as work accidents, occupational diseases and the negative impact of the industry on the surrounding environment, so the level of human work safety as a factor of production is needed so that optimal productivity can be achieved. The application of work safety programs for workers is an important supporting effort in production activities. The work safety program system consists of several program elements and their supporters. In this study the measurement of the results of work safety efforts and the safe T value, the frequency level to express the number of accidents that occur every 1,000,000 hours worked from the employee's